SHARIA ECONOMIC ANALYSIS OF THE IMPLEMENTATION OF SHARIA INSURANCE GUARANTEES - Fazil, Fazil; Zikry, Farhan; Zulaiva Ulya; Hafizh, Muhammad (Progresif : Media Publikasi Ilmiah, 2024)
Sharia insurance is an agreement relating to coverage or guarantee for certain risks of loss. As a health care program, insurance has several objectives, such as protecting oneself, property, objects and commerce as well as economic interests and savings. In the implementation process in Aceh during 2010 there were several things that may not be in accordance with sharia economics. From this the author wants to describe it in journal form. The method the author uses in writing this journal is a descriptive qualitative analysis method of case studies based on literature review. Intensive testing analysis study, using various sources of evidence, both qualitative. As a result, the role and contribution of BPJS to the sustainability of public health insurance is very guaranteed and is felt by the community itself. However, on the other hand, the mechanism that occurs in inputting contains elements of uncertainty, chance and chance which have an impact on gambling and there are indications of usury, namely including fines for delays. Situations like this result in harm to other people or to people who are included in the mechanism process. the. Meanwhile, harm is strictly prohibited in Islam as stated in one of the rules of ushul fiqh.